A Cross‐Cultural Comparison of ICD‐11 Complex Posttraumatic Stress Disorder Symptom Networks in Austria, the United Kingdom, and Lithuania. Issue 1 (28th January 2019) - Knefel, Matthias; Lueger‐Schuster, Brigitte; Bisson, Jonathan; Karatzias, Thanos; Kazlauskas, Evaldas; Roberts, Neil P.
Abstract: The 11th revision of the World Health Organization's International Classification of Diseases ( ICD‐11 ) includes a new disorder, complex posttraumatic stress disorder (CPTSD). The network approach to psychopathology enables investigation of the structure of disorders at the symptom level, which allows for analysis of direct symptom interactions. The network structure of ICD‐11 CPTSD has not yet been studied, and it remains unclear whether similar networks replicate across different samples. We investigated the network models of four different trauma samples that included a total of 879 participants ( M age = 47.17 years, SD = 11.92; 59.04% women) drawn from Austria, Lithuania, and Scotland and Wales in the United Kingdom. The International Trauma Questionnaire was used to assess symptoms of ICD‐11 CPTSD in all samples. The prevalence of PTSD and CPTSD ranged from 23.7% to 37.3% and from 9.3% to 53.1%, respectively. Regularized partial correlation networks were estimated and the resulting networks compared. Despite several differences in the symptom presentation and cultural background, the networks across the four samples were considerably similar, with high correlations between symptom profiles (ρs = .48–.87), network structures (ρs = .69–.75), and centrality estimates (ρs = .59–.82). These results support the replicability of CPTSD network models across different samples and provide further evidence about the robust structure of CPTSD. The most central symptom in all four sample‐specific networks and the overall network was "feelings of worthlessness." Implications of the network approach in research and practice are discussed. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Una comparación intercultural de las redes de síntomas del TEPT complejo de la CIE‐11 en Austria, Lituania y el Reino Unido UNA COMPARACIÓN DE LAS REDES DE TEPT COMPLEJO CIE‐11 La undécima revisión de la Clasificación Internacional de Enfermedades de la Organización Mundial de la Salud (CIE‐11) incluye un nuevo trastorno, el Trastorno de Estrés Postraumático Complejo (TEPT‐C). El enfoque de red para la psicopatología permite la investigación de la estructura de los trastornos a nivel de los síntomas, lo que permite el análisis de las interacciones directas de los síntomas. La estructura de red del TEPT‐C CIE‐11 aún no se ha estudiado, y no está claro si redes similares se replican en diferentes muestras. Investigamos los modelos de red de cuatro muestras de trauma diferentes que incluyeron un total de 879 participantes ( M edad = 47.17 años, DE = 11.92; 59.04% mujeres) extraídos de Austria, Lituania y Escocia y Gales en el Reino Unido. El Cuestionario Internacional de Trauma se utilizó para evaluar los síntomas de TEPT‐C CIE‐11 en todas las muestras. La prevalencia de TEPT y TEPT‐C varió de 23.7% a 37.3% y de 9.3% a 53.1%, respectivamente. Se estimaron las redes de correlación parcial regularizadas y se compararon las redes resultantes. A pesar de varias diferencias en la presentación de los síntomas y los antecedentes culturales, las redes en las cuatro muestras fueron considerablemente similares, con altas correlaciones entre los perfiles de síntomas (ρs = .48 – .87), las estructuras de red (ρs = .69 – .75) y estimaciones de centralidad (ρs = .59 – .82). Estos resultados respaldan la replicabilidad de los modelos de red de TEPT‐C en diferentes muestras y proporcionan más evidencia sobre la estructura robusta del TEPT‐C. El síntoma más central en las cuatro redes específicas de la muestra y la red en general fue "sentimientos de inutilidad". Se discuten las implicaciones del enfoque de red en la investigación y la práctica. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 A cross‐cultural comparison of ICD‐11 Complex PTSD symptom networks in Austria, Lithuania, and UK Traditional Chinese 標題: 奧地利、立陶宛及英國ICD‐11複雜型創傷後壓力症症狀網絡的跨文化比較 撮要: 世界衛生組織公佈的《國際疾病分類》第十一版(ICD‐11), 裡面包含一種新的疾病──複雜型創傷後壓力症(CPTSD)。以網絡分析法研究心理疾病, 使我們可在症狀的層面研究疾病結構, 分析症狀之間直接的相互作用。過往未有研究檢視ICD‐11 CPTSD的網絡結構。而且, 我們仍不清楚在不同樣本中, 是否都會複製出現類似的網絡。我們探查四個不同的創傷樣本的網絡模型, 當中包含879人 (M age = 47.17 歲, SD = 11.92; 59.04% 女性), 他們來自奧地利、立陶宛以及英國蘇格蘭和威爾士。國際創傷問卷用以評估所有樣本的ICD‐11 CPTSD症狀。PTSD與CPTSD患病率值域, 分別為23.7%至37.3%及9.3%至53.1%。我們預測出已調整的淨相關網絡, 並比較所得的網絡。除了在症狀呈現方式和文化背景方面有些差異外, 四種樣本的網絡都頗為相似, 症狀剖象(ρs = .48–.87)、網絡結構(ρs = .69–.75)、中心性預測(ρs = .59–.82)都有高度關連性。以上結果反映CPTSD網絡模型在不同樣本的可複製性, 並進一步證明CPTSD的結構穩固。在四個樣本特殊的網絡和整體的網絡中, 最為中心的症狀乃「一無是處的感覺」。我們亦討論到這次採用網絡分析法所得的結果, 如何有助研究和治療。 Simplified Chinese 标题: 奥地利、立陶宛及英国ICD‐11复杂型创伤后压力症症状网络的跨文化比较 撮要: 世界卫生组织公布的《国际疾病分类》第十一版(ICD‐11), 里面包含一种新的疾病──复杂型创伤后压力症(CPTSD)。以网络分析法研究心理疾病, 使我们可在症状的层面研究疾病结构, 分析症状之间直接的相互作用。过往未有研究检视ICD‐11 CPTSD的网络结构。而且, 我们仍不清楚在不同样本中, 是否都会复制出现类似的网络。我们探查四个不同的创伤样本的网络模型, 当中包含879人 (M age = 47.17 岁, SD = 11.92; 59.04% 女性), 他们来自奥地利、立陶宛以及英国苏格兰和威尔士。国际创伤问卷用以评估所有样本的ICD‐11 CPTSD症状。PTSD与CPTSD患病率值域, 分别为23.7%至37.3%及9.3%至53.1%。我们预测出已调整的净相关网络, 并比较所得的网络。除了在症状呈现方式和文化背景方面有些差异外, 四种样本的网络都颇为相似, 症状剖象(ρs = .48–.87)、网络结构(ρs = .69–.75)、中心性预测(ρs = .59–.82)都有高度关连性。以上结果反映CPTSD网络模型在不同样本的可复制性, 并进一步证明CPTSD的结构稳固。在四个样本特殊的网络和整体的网络中, 最为中心的症状乃「一无是处的感觉」。我们亦讨论到这次采用网络分析法所得的结果, 如何有助研究和治疗。